Laminated structure design of wood—Bamboo hybrid laminated composite using finite element simulations. (November 2016) - Chen, Fuming; Wang, Ge; Li, Xingjun; Simth, Lee M; Shi, Sheldon Q
In order to explore competitive bio-products to meet the requirements of the engineering structural member with high-strength, light-weight and low cost, bamboo bundle and wood laminated veneer lumbers (BWLVLs) with well-designed laminated structures have been regarded as potential candidate. Eight different assemble patterns of BWLVLs were designed and their mechanical performances with elastic range and ultimate bearing failure stage including the deflection, stress distribution, and stress transferring between adjacent layers were investigated using finite element simulations. The results showed that the finite element predicting model with a high accuracy could be used to optimize the design of laminated structures for bamboo bundle and wood veneer laminated composites. The relative error of the simulation results from the predicting model and the experimental results for different laminated composite panels was substantially less than 10%. The rank order for the VonMises stress of eight assemble BWLVLs were (7B) > (BBPPPBB) ≈ (BBPBPBB) > (BPBPBPB) > (BPPPPPB) ≈ (BPPBPPB) > (PBPBPBP) > (7P), (P) poplar, and (B) bamboo. The stress in laminated composites was transferred from poplar layers with low modulus to bamboo bundle layer with high elastic modulus.